Rimbaud : um subalterno híbrido em contexto colonial? - Barbosa, Lohaine Jardim (2011)
That work is going to produce reflections about subalternidade and hibridização, from a reading indiciária of the work and life of Arthur Rimbaud, propondo the reading of Rimabud while a subordinate voice hibrida in colonial context. In the first chapter, building a field of visions/enunciations of the subalternidade present in its works. I detach the "subordinate west", propondo the reading of the "poetic enunciation" of Rimbaud while a subordinate enunciation in colonial context. Upon discussing the poet hibrido, I propose the notion of "subordinate subjectivity" and I emphasize the importance of the theories that try the trials of hybridization for a better comprehension of the complex phenomena of formation and transformation of the subjectivities in conditions of subalternidade. In end, I detach the proposal of approach for enterprising the knowledge and the "I" of the contingency and of the superimposition, present in the poetry of Rimbaud, and empreendo a reflections about the concept of science and the status of the social sciences today, in Brazil contemporary.